The BCL Method for DSSC: Basis and Applications - Mauricio Barrera; Irma Crivelli; Barbara Loeb (Applied Sciences, 2022)
In this work, a comprehensive view of the route that led to the construction of a theoretical approach to the functioning of DSSC is presented. The model was developed based on the theoretical interpretation of experimental results obtained along the years for solar cells including different dyes. This allowed the authors to generate the Barrera, Crivelli, Loeb (BCL) model. The method is based on a system of equations that uses time-dependent density functional theory (TDDFT) calculations to obtain a theoretical index, the Global Efficiency Index (GEI), for the efficiency of a sensitized solar cell. The GEI is obtained through the product of three factors: the available energy for injection, the amount of charge injected, and the efficiency of regeneration. The results so far obtained show a promising correlation with the experimental index of photo conversion efficiency (PCE). Moreover, the method provides theoretical tools that allow us to obtain an understanding of the operation of the cell, and provide us with the keys to optimize it. Its application to other type of devices, as, e.g., the highly more efficient perovskite solar cells, emerges as a challenging future goal.